The relationship between age and length of service and work stress among gas station operators in Watang Sawitto subdistrict, Pinrang Regency - Eyastuti, Eyastuti; Rais, Muh.Kardi; Ali , Muh.yamin; Hasbullah , Hasbullah; Irawan, Mady (Journal of Midwifery and Nursing, 2025)
Work stress is a psychological pressure that can trigger both physical and mental health problems, ultimately affecting employees’ productivity and well-being. This study aims to analyze the relationship between age and length of service with work stress among gas station operators in Watang Sawitto District, Pinrang Regency. The research employed a quantitative approach with a cross-sectional design, involving 32 gas station operators as respondents. Data were collected through structured questionnaires and analyzed using the Chi-Square test. The results showed a significant relationship between age and work stress (p = 0.001), as well as between length of service and work stress (p = 0.002). The novelty of this research lies in its focus on occupational stress factors among gas station operators—a workforce group that is rarely studied despite their exposure to repetitive tasks, environmental hazards, and customer interaction stressors. The practical implications of this study highlight the importance of workplace stress management programs, including periodic psychological assessments and work schedule adjustments, to maintain operator performance and occupational health.